2019
DOI: 10.3390/buildings9040094
|View full text |Cite
|
Sign up to set email alerts
|

Indoor/Outdoor Environmental Parameters and Window-Opening Behavior: A Structural Equation Modeling Analysis

Abstract: In moderate climates, the operation of windows is the most common way to control for thermal comfort. Window-opening behavior (WOB) is a complex process influenced by multiple factors, yet only simple bi-variate analyses between variables obtained from longitudinal datasets have been examined. The goal of this study is to investigate the effects of indoor and outdoor environmental parameters on WOB using a statistical modeling approach called “structural equation modeling.” The results show that the indoor env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…thermal sensation, preferences). In an office space in Washington, 44 it was found that in winter windows were opened mostly to cool down the room and/or to improve air circulation, while in summer and fall occupants opened the windows to cool the room, add some background noise and circulating air.…”
Section: Discussionmentioning
confidence: 99%
“…thermal sensation, preferences). In an office space in Washington, 44 it was found that in winter windows were opened mostly to cool down the room and/or to improve air circulation, while in summer and fall occupants opened the windows to cool the room, add some background noise and circulating air.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of season on window use occurs independently from the end-use. For example, in office buildings, Kim et al [61] showed people were more likely to open windows in the warm season than the cold season. Sun et al [62] found the mode of window-opening by office occupants changed throughout seasons: day and night with no closing during summer and all-closed in winter.…”
Section: Rq1: What Influences Behavior?mentioning
confidence: 99%
“…The outdoor temperature, daily work schedule, and on-off state of airconditioners are the three main factors affecting the final window operating behavior. Other investigations add more complexity to the problem by including further variables like differences in the window opening and closing behavior during the seasons [65], and indoor environmental conditions like "too hot," "background noise," and "air circulation" [61]. Other physical factors, such as wind speed, relative humidity, outdoor PM2.5 concentrations, solar radiation, daylight hours showed significant impact on window-opening probability.…”
Section: Rq1: What Influences Behavior?mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that most previous studies only consider environmental variables as key influential factors of occupants' interaction with windows [15,16,[25][26][27][28][29], different parameters can influence the control on natural ventilation [30,31]. Cali et al [32] monitored changes in indoor thermal environment and window-opening behaviour for four years in apartments in Southern Germany.…”
Section: Introductionmentioning
confidence: 99%